2021
DOI: 10.1038/s41467-021-22035-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for hydrogen incorporation into Earth’s core

Abstract: Hydrogen is one of the possible alloying elements in the Earth’s core, but its siderophile (iron-loving) nature is debated. Here we experimentally examined the partitioning of hydrogen between molten iron and silicate melt at 30–60 gigapascals and 3100–4600 kelvin. We find that hydrogen has a metal/silicate partition coefficient DH ≥ 29 and is therefore strongly siderophile at conditions of core formation. Unless water was delivered only in the final stage of accretion, core formation scenarios suggest that 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 65 publications
11
89
1
1
Order By: Relevance
“…These studies reported significant effects of P, T and fO2 on H metalsilicate partitioning that are consistent with molecular dynamics calculations at extreme P and T (Zhang and Yin, 2012;Li et al 2020, Yuan andSteinle-Neumann, 2020). Finally, empirical relationships have also been established to predict the molten metalsilicate liquid partitioning of H (Clesi et al, 2018;Malavergne et al, 2019;Tagawa et al 2021).…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…These studies reported significant effects of P, T and fO2 on H metalsilicate partitioning that are consistent with molecular dynamics calculations at extreme P and T (Zhang and Yin, 2012;Li et al 2020, Yuan andSteinle-Neumann, 2020). Finally, empirical relationships have also been established to predict the molten metalsilicate liquid partitioning of H (Clesi et al, 2018;Malavergne et al, 2019;Tagawa et al 2021).…”
Section: Introductionsupporting
confidence: 71%
“…The entire database (but Clesi et al, 2018) gives the C and H content of silicate melts at C-saturation. We have selected the experimental studies in which both H and C contents in the silicate melt were determined, thus the recent high-P work by Fischer et al (2020), Fichtner et al (2021 and Tagawa et al (2021) could not be used here (see the 2-next paragraphs). Clesi et al (2018) did not measure the C-content in the silicate melts but C-contents in silicate melts at C-saturation under the P-T-fO2-fH2O conditions of their experiments is mostly provided by other studies.…”
Section: The Databasementioning
confidence: 99%
See 3 more Smart Citations